BLENDED LEARNING: ALTERNATIVE METHODS OF EFFECTIVE ISLAMIC RELIGIOUS EDUCATION - Halid, Ahmad (Program Studi Pendidikan Agama Islam, 2022)
Blended learning is a learning method that combines two things, namely face-to-face learning directly and online using the Learning Management System. Simply put, this learning method combines a face-to-face learning system at school and school from home. This learning method is a teaching process by combining teacher-led learning activities using pictures, videos, digital assignments, and face-to-face discussions. Classrooms provide opportunities for students and teachers to be able to carry out the face-to-face teaching and learning process directly. While online learning provides opportunities for teachers to provide independent learning using eLearning components such as games, learning videos, and online quizzes. One of the biggest challenges for schools to implement blended learning methods is the absence of a supportive learning management system. In fact, a qualified learning management system is one of the keys to the success of the blended learning method. Because by having a qualified learning management system, teachers can easily arrange modules, exams, or assessments for all students